The effect of treatment with melatonin on primary school aged children with difficulty in initiation and maintenance of sleep - Jalilolghadr, Shabnam; Roozmehr, Sasaan; Yazdi, Zohreh; Soltanabadi, Mahdi (The Turkish Journal of Pediatrics, 2022)
Background. The present study was designed to evaluate the effect of melatonin on the sleep initiation, duration of sleep, quality of sleep and daily performance in healthy children suffering from insomnia. Methods. This study was done as a double blind randomized clinical trial in the sleep clinic of Qods Hospital. Sixty healthy children between 7 and 12 years of age having sleep problems were chosen and randomly divided in interventional and placebo groups. Before the treatment, children`s sleep habits questionnaire (CSHQ) was filled in both groups. Then, both groups were taught about sleep hygiene. Afterwards, the intervention group was treated with 3mg nocturnal dose of melatonin for one month and the other group with a placebo. Then, CSHQ was filled again for both groups. The intervention was Melatonin. The mean analyzed results of the variants in pre-test and post-test were compared and p < 0.05 was regarded as significant. Results. Results showed that Melatonin with no side effect is effective in improving: 1- The initiation and maintenance of sleep, 2- Sleep onset delay, 3- Sleep duration, 4- Sleep anxiety, 5- Nightly awakenings 6- Parasomnias and 7- daily performance; but is ineffective in bedtime resistance and sleep disordered breathing. Conclusions. Our results indicate that melatonin is more effective than placebo in improving the initiation and maintenance of sleep and most of its subscales in primary school aged children.
Keywords: difficulty in initiation and maintenance of sleep; melatonin; primary school aged children